Monte Carlo Simulation of Ferroelectric Behavior in PZT Films by Using a Stress Dependent DIFFOUR Hamiltonian (2014)
In this work the polarization and hysteresis response of Lead Zirconate Titanate (PZT) ferroelectric thin films was studied in relation to the variation on temperature, stress, electric field and the content of non-ferroelectric impurities by using a Mont